Lipidation of NOD2 Agonists with Adamantane and Stearoyl Moieties Differentially Regulates Their In Vivo Adjuvant Activity - Samo Guzelj; Marcela Šišić; Špela Bizjak; Leo Frkanec; Ruža Frkanec; Žiga Jakopin (MDPI AG, 2022)
NOD2 is an innate immune receptor that constitutes an important target for the development of small molecule immunopotentiators with great potential to be used as vaccine adjuvants. We report here the results of an in vivo study of the adjuvant properties of a desmuramylpeptide NOD2 agonist SG29 and its lipidated analogs featuring an adamantyl moiety or a stearoyl group. These compounds have been synthesized, incorporated into liposomes, and evaluated for their in vivo adjuvant activity. The characterization of liposome formulations of examined compounds revealed that their size increased in comparison to that of empty liposomes. The introduction of a stearoyl or an adamantane lipophilic anchor into the structure of SG29, to produce SG115 and ZSB63, respectively, substantially improved the in vivo adjuvant activity. Of note, the attachment of the stearoyl moiety produced a Th2-biased immune response, while the incorporation of the adamantyl moiety greatly enhanced the production of total IgG but mostly augmented the production of IgG2a antibodies, which indicated a shift toward a Th1 immune response. The identified bona fide capacity of ZSB63 to initiate a cellular immune response thus highlights its untapped potential as an alternative vaccine adjuvant.